2018
DOI: 10.3727/152599518x15252895715050
|View full text |Cite
|
Sign up to set email alerts
|

It's a Once-in-a-Lifetime Experience and Opportunity—Deal with it! Volunteer Perceptions of the Management of the Volunteer Experience at the London 2012 Olympic Games

Abstract: Mega-events such as the Olympic Games involve huge numbers of volunteers from the host community, necessitating the development of a large volunteer program, which will only operate for a short time. Leveraging this volunteer energy to lead to longer-term community volunteering has become a legacy goal for many event organizers. Mega-events typically use a top-down "program management" approach for their volunteer program. This article examines how the program management style impacts on the volunteer experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…Their analysis suggested that the London 2012 Olympics used a program-centred approach to volunteer management rather than a more personal membership-centred approach, which caused irritation to volunteers and strained their commitment to the event. This theme was further explored in Holmes, Nichols, and Ralston (2018) through a qualitative study which interviewed volunteers about their experiences throughout the recruitment, training and delivery of the event.…”
Section: Event Volunteer Management and Selectionmentioning
confidence: 99%
“…Their analysis suggested that the London 2012 Olympics used a program-centred approach to volunteer management rather than a more personal membership-centred approach, which caused irritation to volunteers and strained their commitment to the event. This theme was further explored in Holmes, Nichols, and Ralston (2018) through a qualitative study which interviewed volunteers about their experiences throughout the recruitment, training and delivery of the event.…”
Section: Event Volunteer Management and Selectionmentioning
confidence: 99%
“…Future volunteering intentions are reliant on positive volunteer experiences in relation to recruitment, volunteer application, selection and training program as well as effective and supportive management and administrative processes including rostering and related processes (Nichols and Ralston, 2012). Research suggests that inflexible or unsuitable volunteer recruitment and management processes that are not appropriately tailored result in a negative volunteer experience with implications for future volunteering intentions (Holmes et al , 2018). Other factors such as demographics, the role of the media, volunteering motivations, and previous volunteer experience have been found to have implications for future volunteering intentions (Dickson et al , 2014; Tomazos and Luke, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has identified that mega sporting events present a challenging management environment due, in part, to the significant numbers of volunteers involved in operating these events and also the intense, short-term nature of the event (Holmes et al , 2018; Lockstone and Baum, 2009). The complexity of reviewing and assessing such significant numbers of applications within the recruitment process, and the outcomes of that process in terms of candidate selection and disappointing unsuccessful applicants would, ideally, be considered when designing a supportive volunteer recruitment process (Lockstone and Baum, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As described below, official access to researching volunteers at 2012 was restricted to academics working with Nielsen. Other academics have researched volunteering at the Games, but have been restricted to using small, independently recruited samples (e.g., Holmes, Nichols, & Ralston, 2017).…”
Section: Researching the 2012 London Olympic And Paralympic Gamesmentioning
confidence: 99%